Vocatives in Yemeni (IBBI) Arabic: Functions, Types and Approach. (25th February 2019) - Shormani, Mohammed Q
Abstract: In this paper, I investigate vocative expressions in Ibbi Arabic, a dialect of Yemeni Arabic, and a very under-investigated language variety. I examine this phenomenon in terms of functions, types and approach. The study shows that vocatives in Yemeni Arabic have several and various social/pragmatic functions, and that any constituent and any syntactic category including nouns, adjectives, deverbals, finite and nonfinite clauses, pronouns, etc. can be vocativized. The paper argues and provides empirical syntactic evidence for syntax as the most adequate approach to analysing vocatives in Yemeni Arabic, thus, supporting current mainstream thought in this regard.